Year level fluctuations of misconceptions on the different dimensions of force among physics majors - Malayao, Sotero O., Jr (Transactions of the National Academy of Science and Technology, 2011)
This study is an attempt to unravel the cognitive structure regarding the concept of force, among physics majors, as it is decomposed into its nine sub-dimensions. The scope of the sample covers both BS and BSEd students represented by year level. The study utilized the Force Concept Inventory (FCI) in which available studies in Philippine set-up involved only, in most cases, its usage as a construct to correlate with other cognitive random sampling and were given the FCI after their classes. By dissecting every dimensions of force, the study yielded very interesting results that are deemed important for curriculum developers: (i) that misconceptions does diminish with increasing year level in terms of gross count with the third year having the least average misconception over the fourth year, (ii) that there are is an interesting though inconsistent fluctuations, in the third year at first based on average percent of misconceptions, (iii) that there is indeed an incoherent of misconceptions among the respondents. One big implications of the study is the needed to investigate in depth the different dimensions of force by covering bigger demographics in order that a conclusive status can be established.